Assessing synchronous removal of nutrients and SMX based on novel Mn-C composites: Impact of different proportion of manganese dioxide - Jia, Lixia; Qi Zhou; Li, Yuanwei; Wu, Weizhong (CHEMICAL ENGINEERING JOURNAL, 2023)
In this study, Mn-C composites using different MnO2 contents and solid carbon material were prepared to explore the synchronous removal performance of nutrients and SMX. Higher nitrate removal performance (97-98 %) with quickest nitrate removal rate (4.97 mg N L -1h- 1) was obtained in Mn_20 systems. The increased Mn content and Mn-P compound were observed via surface characteristics, indicating the involvement of MnOx in pollutants removal, particularly for higher phosphorus removal (84-89 %) via Mn-P precipitation and BioMnOx adsorption. Nevertheless, compared to systems based on Mn_0 composites (74 %), systems with Mn-C composites presented lower SMX reduction efficiency (34-51 %), which might be attributed to the large Mn(II) accumulation, impairing certain microbes and lower the MnOx function. Higher abundance of genera affiliated to Bacter-oidetes_vadinHA17 and Rhodocyclaceae was observed in the Mn-C composites, as well as the gathering of Geo-bacter and Desulfovibrio as keystone taxa, responsible for the removal of nitrate and SMX and microbial interactions. Besides, the increase of sulfonamide ARGs was closely related to the predominant microbes in the Mn-C composites, which acted as the hosts of ARGs. This study broadens the knowledge of Mn-C composites in synergetic removal of nutrients and organics, and supports the potential application of manganese oxide in wastewater treatment.